The Effect of Machining Parameters and Drill Point Angle on the Temperature Distribution in AISI 304 Stainless Steel During Dry Drilling Operation - Kadhim, Amjed M.; Hassan, Abdulkareem F.; Rishack, Qais A. (Basrah Journal for Engineering Sciences, 2021)
In this research work, the influence of cutting parameters and drill point angle on the temperature distribution in dry drilling of stainless steel AISI 304 was numerically investigated by using FE method based on DEFORM-3D V.11 commercial software. Two cutting tools of 10 mm diameter but different in point angles, one is 110° and the other is 118°. These tools were imported from specific website in a format of STL and inserted in the program during modeling of cutting tools. The material of the cutting tools is selected as high-speed steel. The workpiece model is created as cylindrical shape with 50 mm diameter and 5 mm thickness. The cutting parameters are selected as three cutting speeds (100, 200, and 300) rpm, with three feed rates (0.15, 0.25, and 0.35) mm/rev. The depth of hole is fixed for all simulations (3 mm). The percentage of increase or decrease in the resulted temperature according to the various cutting parameter was also calculated and discussed. The best cutting performance of tools according to the change of point angles was also investigated. The results provided a significant influence of cutting speed and tool point angle on the temperature generated in the machined models and very small influence of feed speed on the workpiece temperature.